2007
DOI: 10.1159/000107770
|View full text |Cite
|
Sign up to set email alerts
|

17-Beta-Estradiol Directly Regulates the Expression of Adrenergic Receptors and Kisspeptin/GPR54 System in GT1-7 GnRH Neurons

Abstract: Estradiol plays a critical role in the feedback regulation of reproduction, in part by modulating the neurosecretory activity of gonadotropin-releasing hormone (GnRH) neurons. While indirect effects of estradiol on GnRH neurons have been clearly demonstrated, direct actions are still controversial. In the current study, we examined direct effects of 17β-estradiol upon the expression of receptors for afferent signals at the level of the GnRH neuron, using immortalized GT1-7 cells. Using RT-PCR, we confirmed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 137 publications
5
23
0
1
Order By: Relevance
“…Although most studies have demonstrated a stimulatory role for KISS1 on GnRH release, KISS-10 (1-10 nM) can significantly stimulate Gnrh mRNA expression in GT1-7 cells [36]. A direct effect of grouper Kiss2-10 on gnrh1 is consistent with the situation in mammals where KISS1 regulates Gnrh1 (mammalian gnrh).…”
supporting
confidence: 64%
“…Although most studies have demonstrated a stimulatory role for KISS1 on GnRH release, KISS-10 (1-10 nM) can significantly stimulate Gnrh mRNA expression in GT1-7 cells [36]. A direct effect of grouper Kiss2-10 on gnrh1 is consistent with the situation in mammals where KISS1 regulates Gnrh1 (mammalian gnrh).…”
supporting
confidence: 64%
“…Kisspeptin was demonstrated to increase the intracellular calcium concentration [Ca 2C ] i in isolated GnRH neurons (Kroll et al 2011) as well as in hypothalamic GT1-7 immortalized cell lines (Ozcan et al 2011). Furthermore, GnRH secretion was increased in kisspeptin-activated GT1-7 cells (Jacobi et al 2007, Novaira et al 2009, Tonsfeldt et al 2011. Taken together, these findings implicate an important role for kisspeptin/GPR54 for the regulation of sexual maturation and the development of the reproductive system.…”
Section: Introductionmentioning
confidence: 84%
“…Kisspeptin has been shown to be a key component in the regulation of GnRH secretion [14,15,36,37], and investigations have correlated GnRH gene expression to secretion in response to kisspeptin stimulation [17,18]. Our recent studies aimed at elucidating the mechanism of GnRH gene regulation and the activation of the GnRH promoter by kisspeptin have provided new insight into possible mechanisms regulating GnRH gene expression [7,18,38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on the role of kisspeptin in the GnRH neuron have largely focused on cellular secretion of GnRH [14][15][16], and interestingly, more recent studies have related GnRH gene expression to secretion in response to kisspeptin stimulation [7,17,18]. Furthermore, in this context, through our previous studies using mouse-derived immortalized GnRH-secreting neuronal cell lines (GT1-7 and GN11) and transgenic mouse models, we have investigated the role of kisspeptin in modulating GnRH transcription/translation activity [7].…”
Section: Introductionmentioning
confidence: 99%